Reference intervals for hematology, serum biochemistry and blood gas parameters in Indian elephants (Elephas maximus indicus) under human care - Muliya, Sanath Krishna; Bindhani, Uddalak Tathagato; Kawlni, Lallianpuii; Ramakrishna, Anjan Kumar; Mirza, Vaseem; Rahman, Mujib Ur; Kumar, Vinay; Huchhaiah, Ramesha; Kuttappa, Thammaiah Chekkera; Sharma, Souritra; Hussain, Kafil; Kolipakam, Vishnupriya; et al. (Frontiers in Veterinary Science, 2025)
The Indian elephant (Elephas maximus indicus), classified as “Endangered” by the IUCN, faces significant population declines and habitat degradation, necessitating robust health assessment tools for both managed and free-ranging populations. This study aimed to establish comprehensive hematology, serum biochemistry and arterial blood gas reference intervals (RIs) for Indian elephants, addressing gaps in existing studies, and following the guidelines of the American Society for Veterinary Clinical Pathology (ASVCP). Samples were collected from a well-defined elephant population under human care in southern India and analyzed on the same day. Phlebotomy was carried out in unsedated elephants in lateral recumbency to avoid sedation-related effects on measurands. A total of 92 elephants were sampled. Hematology RIs were derived from EDTA whole blood using automated methods, while serum biochemistry RIs were generated using semi-automated analyzers; arterial blood gas analysis was also performed using a portable field analyzer. The established hematology RIs were as follows: Hb 8.62–16.78 g/dL, RBC 1.77–4.9 × 1012/L, PCV 21.73–49.25%, MCV 112.49–131.39 fL, MCH 39.3–62.39 pg./cell, MCHC 33.40–41 g/dL, platelet count 171.57–947.1 × 103/μL, WBC 9912.5–29,475 cells/μL. Serum clinical chemistry RIs included: SGPT 4.01–20.34 U/L, ALP 124.89–556.68 U/L, TP 5.54–9.3 g/dL, albumin 2–2.91 g/dL, globulin 3.36–6.9 g/dL, GGT 2.38–23.18 U/L, CRT 0.65–2.06 mg/dL, BUN 4.12–24.32 mg/dL, and albumin/globulin ratio 0.3–0.8. Serum lipid profile RIs were: TC 26.96–69.39 mg/dL, triglycerides 12.55–52.47 mg/dL, HDL 9.02–39.38 mg/dL, LDL 4.63–49.07 mg/dL, and VLDL 2.52–10.5 mg/dL. Serum electrolyte RIs included: Ca 6.21–11.38 mg/dL, P 2.89–6.29 mg/dL, Na 133.94–174.77 mmol/L, K 1.83–7.81 mmol/L, and Cl 92.56–119.46 mmol/L. Arterial blood gas parameters were: pH 7.368–7.515, pCO₂ 28.5–47.9 mmHg, pO₂ 71.0–120.8 mmHg, cHCO₃− 23–30.1 mmol/L, sO₂ 94.4–99.6%, and tCO₂ 22.8–29.5 mmol/L. These RIs provide critical baseline data for health monitoring, enabling the detection of subclinical infections and evaluation of physiological, nutritional, and ecological welfare. By enhancing our understanding of the species’ physiological norms, this study supports improved veterinary care and conservation strategies, ultimately contributing to the long-term survival and welfare of Indian elephants in the region.